Corporate control and firm value: The bright side of business groups. Issue 2 (June 2017) - Torres, Juan Pablo; Jara Bertín, Mauricio; López-Iturriaga, Félix J.
Abstract: We analyze the effect of pyramidal ownership levels on the performance of Chilean firms by considering the impact of business groups. Using an unbalanced panel of 1018 firm-year observations from 88 quoted firms for the period from 2000 to 2014, we find that higher levels of separation between ownership rights and control rights decrease performance in family firms that are not part of a business group. This result suggests that too much separation of ownership and control rights in family firms can result in deviant incentives for family members to extract private benefits. However, we also find that group affiliation reduces the negative impact of the separation of ownership and control rights in family firms, which corroborates the bright side of internal capital markets for these firms.